Light Microscopic Study of Renal Morphological Alterations in Spontaneously Hypertensive Rats - Stancho Stanchev; Alexandar Iliev; Lina Malinova; Boycho Landzhov; Georgi Kotov; Dimka Hinova-Palova (Journal of Biomedical & Clinical Research, 2017)
The impact of hypertension on the kidney is associated with a number of morphological changes, which gradually lead to development of end-stage kidney disease. The aim of the present study was to trace the postnatal histological changes in the morphology of nephrons and renal interstitium in spontaneously hypertensive rats. In this study, we described and compare alterations in renal histology as a consequence of hypertension in two age groups of spontaneously hypertensive rats, aged 2 and 6 months (n=3; per age group). The description of the alterations in renal morphology was made by light microscopic analysis using routine haematoxylin and eosin staining, periodic acid Schiff (PAS) reaction and Mallory’s trichrome staining. We did not observe significant changes in renal histology in 2-month-old rats: renal corpuscles were relatively well preserved, proximal and distal tubules were clearly demarcated, and no pathological changes in the larger intrarenal blood vessels were found. There was evidence of glomerular and tubular basement membranes thickening and focal interstitial fibrosis. In 6-month-old rats, we noted pronounced glomerulosclerosis, periglomerular and periarteriolar fibrosis and expansion of interstitial fibrosis. The vascular alterations depended on the size of the blood vessels and included hyaline arteriosclerosis, fibrinoid necrosis and myointimal thickening of interlobular arteries. Untreated hypertensive nephrosclerosis is associated with progressive renal alterations, which cause impaired renal function – a lifelong limiting factor.